A modeling framework to meta-analyse discard survival experiments illustrated by Nephrops norvegicus in European demersal trawl fisheries - M. Morfin; E. Savina; H.P. Benoît; M. Teixeira Alves; A. Albalat; T. Catchpole; C. Fox; M. McHugh; S. Méhault; H. Nilsson; M. Oliver; D. Valentinsson; et al. (Fisheries Research, 2025)

Whole Genome Sequencing Reveals How Plasticity and Genetic Differentiation Underlie Sympatric Morphs of Arctic Charr - Khrystyna Kurta; Mariano Olivera Fedi; Kendall Baker; Tom Barker; Leah Catchpole; Claudio Ciofi; Arianna Cocco; Joanna Collins; Genevieve Diedericks; Maria Angela Diroma; Alex Durrant; Kjetil Hindar; et al. (Molecular Ecology, 2025)
Salmonids have a remarkable ability to form sympatric morphs after postglacial colonisation of freshwater lakes. These morphs often differ in morphology, feeding and spawning behaviour. Here, we explored the genetic basis of morph differentiation in Arctic charr ( n = 283) by first establishing a high‐quality reference genome and then using this in whole genome sequencing of distinct morphs present in two Norwegian and two Icelandic lakes. The four lakes represent the spectrum of genetic differentiation between morphs from one lake with no genetic differentiation between morphs, implying phenotypic plasticity, to two lakes with locus‐specific genetic differentiation, implying incomplete reproductive isolation, and one lake with strong genome‐wide divergence consistent with complete reproductive isolation. As many as 12 putative inversions ranging from 0.45 to 3.25 Mbp in size segregated among the four morphs present in one lake, Thingvallavatn, and these contributed significantly to the genetic differentiation among morphs. None of the putative inversions were found in any of the other lakes, but there were cases of partial haplotype sharing in similar morph contrasts in other lakes. Our findings are consistent with a highly polygenic basis of morph differentiation with population‐specific selection on alleles linked to the development of similar morph phenotypes. The results support a model where morph differentiation is first established through phenotypic plasticity, leading to niche expansion and separation. This may be followed by gradual development of reproductive isolation, locus‐specific differentiation and eventually complete reproductive isolation and genome‐wide divergence.

Scratch circles and circular purported ammoglyphs: Novel observations from the Cape south coast of South Africa - Charles W. Helm; Robin M. Catchpole; Hayley C. Cawthra; Richard M. Cowling; Jan C. De Vynck; Mark G. Dixon; Renée Rust; Willo Stear; Guy H.H. Thesen (Proceedings of the Geologists' Association, 2024)

Hyper-stimulation of Pyrococcus furiosus CRISPR DNA uptake by a self-transmissible plasmid - Elizabeth A. Watts; Sandra C. Garrett; Ryan J. Catchpole; Landon M. Clark; Brenton R. Graveley; Michael P. Terns (Extremophiles, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

The Case for an Early Biological Origin of DNA - Anthony M. Poole; Nobuyuki Horinouchi; Ryan J. Catchpole; Dayong Si; Makoto Hibi; Koichi Tanaka; Jun Ogawa (Journal of Molecular Evolution, 2014)

Involving stakeholders in the commissioning and implementation of fishery science projects: experiences from the U.K. Fisheries Science Partnership a - M. J. Armstrong; A. I. L. Payne; B. Deas; T. L. Catchpole (Journal of Fish Biology, 2013)
Following from similar initiatives worldwide, the U.K.'s Fisheries Science Partnership ( FSP ) was established in 2003 to provide the fishing industry with opportunities to propose and participate in scientific studies in collaboration with fishery scientists. Key concepts were that most of the available funding would support industry participation, that industry, not scientists, would come up with the ideas for projects, and that commercial fishing vessels and fishing methods would be used to address specific concerns of the fishing industry in a scientifically controlled manner. Nearly 100 projects had been commissioned by March 2012, covering annual time‐series surveys of stocks subject to traditional assessment, and ad hoc projects on, e.g . gear selectivity, discard survival, tagging and migration and fishery development. The extent to which the results of the projects have been used by stakeholders, fishery scientists and fishery managers at a national and E.U . level is evaluated, along with the degree of industry interest and involvement, and reasons are identified for successes or failures in the uptake of the results into management and policy. Finally, the question is posed whether the programme has been successful in improving the engagement of the fishing community in the science–management process and in fostering communication and greater trust between fishers, scientists and managers.

Improved Recovery of Antibiotic-Stressed Microorganisms on Inclusion of Saponin in Aerobic Blood Culture Media - T. S. J. Elliott; C. M. Stevens; F. Macrae; I. T. Hart; D. E. Healing; M. Palmer; C. R. Catchpole (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Improved recovery of antibiotic-stressed microorganisms on inclusion of saponin in aerobic blood culture media - T. S. J. Elliott; C. M. Stevens; F. Macrae; I. T. Hart; D. E. Healing; M. Palmer; C. R. Catchpole (European Journal of Clinical Microbiology & Infectious Diseases, 1998)